2007
DOI: 10.1002/hbm.20499
|View full text |Cite
|
Sign up to set email alerts
|

Tactile‐associated fMRI recruitment of the cervical cord in healthy subjects

Abstract: Using spinal cord functional magnetic resonance imaging (fMRI), 12 right-handed healthy subjects were scanned during a tactile stimulation of the palm of the right hand. The task-related mean signal change was computed for all activated voxels within the cervical cord, and separately, in the four cord quadrants (right and left anterior, right and left posterior) from C5 to C8. The frequency of fMRI activity at each cord level was obtained by assigning a score of 25% at each active quadrant and by averaging the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 36 publications
(66 reference statements)
2
23
0
Order By: Relevance
“…Consistent with the expected regions of neuronal involvement for a tactile stimulation of the palm of the right hand16 17 and with previous cord fMRI studies,8–10 15 18 19 both control subjects and MS patients showed a functional lateralisation of cord activity, which was predominant in the cord side ipsilateral to the stimulus, and a more frequent activation of the posterior than of the anterior cord quadrants. Moreover, all subjects showed cervical cord fMRI activity not only dorsally and at the level corresponding to the dermatome where the stimuli were applied, but also ventrally and in upper cervical cord segments.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with the expected regions of neuronal involvement for a tactile stimulation of the palm of the right hand16 17 and with previous cord fMRI studies,8–10 15 18 19 both control subjects and MS patients showed a functional lateralisation of cord activity, which was predominant in the cord side ipsilateral to the stimulus, and a more frequent activation of the posterior than of the anterior cord quadrants. Moreover, all subjects showed cervical cord fMRI activity not only dorsally and at the level corresponding to the dermatome where the stimuli were applied, but also ventrally and in upper cervical cord segments.…”
Section: Discussionsupporting
confidence: 88%
“…Using a block design (ABAB), where four periods of rest were alternated with four periods of activity (each period of rest and activity consisting of five scans), the subjects were scanned while administering a tactile stimulation of the palm of the right hand, as described elsewhere 8 10 15. To prevent movements of the shoulder, arm, elbow or forearm, subjects' arms were restrained with straps.…”
Section: Methodsmentioning
confidence: 99%
“…These challenges include the small physical dimensions of the spinal cord, poor magnetic field homogeneity in the cord due to magnetic susceptibility differences and motion of the spinal cord and cerebral spinal fluid motion. However, such challenges have now been overcome or reduced, with the development of novel techniques by our laboratory and others [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…By accommodating the small-diameter structures, proton attenuation weighted spin-echo imaging methods can provide high quality images of the brain stem and spinal cord. 13,16,17 For information on the effectiveness of using fast spin-echo imaging methods in the spinal cord and brain stem see Stroman et al 18 The purpose of this study was to use an established spinal fMRI method [17][18][19] to map areas of neuronal activity in the brain stem and cervical spinal cord that are involved with touch and brush sensations in healthy volunteers. We hypothesize that the full distribution of sensory activity from touch and brush stimuli can be reliably mapped in intact human volunteers by means of spinal fMRI.…”
mentioning
confidence: 99%